Implementasi Quality Assurance Sebagai Upaya Peningkatan Mutu Sumber Daya Manusia Di Lembaga Pendidikan Formal - Much Solehudin (STAI Sufyan Tsauri Majenang, 2021)
Quality educational institutions are educational institutions that are able to prioritize the quality of human resources, manage management systems well and are able to provide service satisfaction to customer desires. A leader who has potential in his field can certainly understand quality in an educational environment. Actors in the world of education recognize their obligation to achieve this quality and convey it to their students. This research is included in the category of qualitative research. Data collection techniques by interview, observation and documentation. Data analysis techniques consisted of data reduction, data presentation and data verification. The results of the study indicate that in implementing Quality Assurance as an effort to improve the quality of human resources, there are several things that must be done by the principal of the madrasah / school including making a team, strengthening the vision, mission and objectives of the institution, analyzing problems, determining quality policies, determining standards quality, Determine the procedure. In addition, several policies carried out by the head of madrasah / school in the quality assurance system as an effort to improve human resources are: 1) planning and implementing an overall academic quality assurance system in the form of a Standard Operating Procedure (SOP) as a guideline that teachers and staff must have. , 2) Making instruments and documents needed in the implementation of quality assurance in the form of rules or regulations in force, 3) Conducting training in order to improve the quality of human resources, as evidenced by training reports, 4) Developing a quality assurance information system, through operators madrasah in the implementation of inputting student data, and 5) Reporting every month the implementation of the quality assurance system in a monthly evaluation meeting.